The Role of the Teacher in Improving the Communicative Character of Elementary School Students Through PKn Learning at SDN 03 Pabuaran Cibinong - Khaidir Fadil; Rahmawati Rahmawati (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
This study aims to describe the teacher's role in improving the communicative character of the Civics learning process at SDN 03 Pabuaran . Cibinong is a type of qualitative research that uses descriptive methods to describe the teacher's role in instilling communicative values into Civics lessons . To obtain research data, researchers used two sources, namely primary data and secondary data. Primary data sources used by primary information sources are Civics subject teachers . Secondary data in the form of journals and books. Data collection techniques used are observation and interviews. The data analysis technique uses interaction model analysis according to Miles and Huberman , namely data reduction (data reduction ), data representation (data representation) and plotting results ( validation ). The results of this study indicate that the teacher has carried out his role as a learning resource, facilitator, class manager, demostator , mentor, motivator and evaluator both inside and outside of learning. In addition, the teacher always guides and guides students who cannot show communication personality, by always inviting students to participate in discussions, then creating heterogeneous study groups, helping students who have difficulty expressing opinions orally and in writing. As well as reminding students who still do not speak well and politely to teachers and peers